Biodentine as an Ideal Biomimetic Dental Material for Minimally Invasive Dentistry - Syed Jaffar Abbas Zaidi et al; Shakeel Kazmi (ziauddin University, 2024)
Minimally invasive dentistry (MID) is an evidence based approach which mostly focuses on the repair and regeneration of dental tissues by dental materials. MID encompasses all dental specialities from minimally invasive approach to oral surgeries and impactions, minimally invasive restorative procedures, socket preservation techniques to minimally invasive cavity preparations to minimally invasive approach to caries control. There is a need to investigate the dental biomaterials proposed for MID in terms of their ease of use, bioactivity, biocompatibility, microleakage and longevity. An electronic search was performed in databases included PubMed, Scopus, and SciELO etc. with keywords: "dental biomaterials" and "minimally invasive dentistry". Studies revealed that two commercially available products Mineral Trioxide Aggregate and Biodentine are first-line dental biomaterials for minimally invasive dentistry. Biodentine, a novel biomimetic and bioactive by Septodont, fulfils the goals of minimally invasive dentistry due to its bioactivity and enhanced biomechanical properties. Material testing needed to market this material has been critically analysed in light of the current standards and guidelines with due emphasis given to the drawbacks of Biodentine and remedies proposed in the form of another bioactive material, which could revolutionize the world of minimally invasive dentistry as the ultimate replacement material for enamel, dentin, and cementum. Keywords: Minimally Invasive Surgical Procedures; Biomimetic Materials; Dentistry.